Multielement analysis in serum of healthy population of the metropolitan region of Rio de Janeiro in Brazil by SRTXRF. (30th July 2015) - Canellas, Catarine G. L.; Carvalho, Silvia M. F.; Leitão, Roberta G.; Bellido, Alfredo V. B.; Anjos, Marcelino J.; Lopes, Ricardo T.
Abstract : The determination of multielemental concentrations in physiological fluids is of considerable interest in clinical chemistry. Since it has been established these levels in human serum can be utilized as indicators for several pathological conditions. The multielement composition determination in human serum is important for the investigation of their role in human physiology and metabolism. From this research, more detailed studies on the health of individuals living in the metropolitan region of the state of Rio de Janeiro can be realized in order to improve the quality of life of these individuals. We studied 180 healthy volunteers (80 males and 100 females) aged 19 to 60 years. All the serum samples had been collected of people who live in the urban area of Rio de Janeiro City/Brazil. The measurements were performed at the X‐Ray Fluorescence Beamline at the Brazilian National Synchrotron Light Laboratory (LNLS), in Campinas, São Paulo. We were able to determine the concentrations of the following 11 elements: Na, P, S, Cl, K, Ca, Fe, Cu, Zn, Br and Rb. In this study, we used statistical analysis for the principal components. We were able to verify the presence of two factors that divided the elements into two groups: group 1 formed by elements: Cl, K, S and Ca and group 2 by elements Cu and Zn. Copyright © 2015 John Wiley & Sons, Ltd.